(3OQhS GdYQhVs - (3GHf GdOgGf GdHZOGOj , SYjO Hf GdeHGQc Hf Ydj GdCfUGQj, CHh eMeO,J (B569 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe CHheMeO SYjO Hf GdeHGQc GdfMhj QMeI Gddg CYde Cf GdTYQ daX ehRhf ebai jOd Ydi eYfj s
(3BNQgG (B:s
(3JeJ GdbUjOI GdeCehfI GdeSeGI HMOjbI GdRgQI YOGjGJ GdbQ ddEeGe GdLYHQj s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B100 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B229s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B471s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3YQhV (B186) s
Keywords: (3GdYQhV hGdbhGais